Service Quality And Corporate Image To The Customer Loyalty Of BPRS Baktimakmur Indah Sepanjang Sidoarjo - Nikmah, Rochmatin; Syarifudin, Syarifudin (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2021)
In line with the increasingly intense business competition in all sectors, Islamic banking needs to enhance the company's quality to compete and maintain its existence. One of the keys to success is building customer loyalty. This study aimed to analyze the effect of service quality and corporate image on customer loyalty of BPRS Baktimakmur Indah Sepanjang, Sidoarjo. This research was associative quantitative research, data collection was done through observation and questionnaires with the purposive sampling method. The results revealed that service quality had no significant effect, while corporate image had a significant effect on customer loyalty. However, it simultaneously indicated a quite strong influence. This study found that the indicator with the most dominant influence on service quality was fulfilled expectations, especially in terms of pick-up service. Meanwhile, the corporate image was an indicator of company characteristics, especially the location of the BPRS which was strategic and easily accessible. Thus, it is hoped that the BPRS Baktimakmur Indah Sepanjang, Sidoarjo can enhance service and product quality and be able to maintain its reputation consistently.